Studies on antecedent factors of persistent practice of female circumcision in Abia state, south east Nigeria - Nwosu, Udochi M.; Awa, Madu J.; Enukeme, Juliet U. (International Journal Of Community Medicine And Public Health, 2017)
Background: Despite the ban of female circumcision (FC) in Nigeria in 2003, the practice has continued to persist. This study is aimed at identifying antecedent factors contributing to its persistent practice in rural communities of Nigeria and recommend ways of stopping the practice completely. Methods:A Multi-stage probability sampling method was used in selecting ten rural communities in Isiala Ngwa South Local Area of Abia State, South East Nigeria. A total of 4303 mothers of female children were enumerated. A sample size of 860 mothers was systematically selected. Instrument for data collection was a pre-tested structured questionnaire. Data were analyzed quantitatively and qualitatively. Results: Socio-demographic and economic factors that significantly contribute to persistent practice of FC include; age of mothers, occupation, level of education and monthly income (P<0.005). Other antecedent factors are lack of awareness of health consequences of FC, local tradition and cultural imperative, illusory fears, perceived belief and rationalization. About 63.2% of respondents opined that the best way to stop the practice is through health education and promotion campaign at the grass root to increase knowledge and awareness of FC and its adverse health implications. Conclusions:Several factors contributed to persistent practice of FC and ranging from socio-demographic and economic factors to ignorance and rationalization. These factors can be addressed by promoting health education and awareness campaign and strict enforcement of the ban through prosecution of offenders.